2020
DOI: 10.35691/jbm.0202.0142
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anthropic Pressure on the Quality and Diversity of Groundwater in the Region of Sighus Oum-El-Bouaghi and El Rahmounia, Algeria.

Abstract: Groundwater of Oum-El-Bouaghi and its surroundings hosts a variety of microflora and fauna. This study investigated the relationship between the effect of human activity and the biodiversity and distribution of aquatic fauna in two semi-arid regions Sighus region (Oum-El-Bouaghi) and El Rahmouni (Constantine) in north-eastern Algeria. Fourteen wells and six springs were studied in two hydrographic basins, that of Constantine and Seybouse Melegue. Significant differences were revealed between the wells and spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…According to Rodier(2009), groundwater is less sensitive to temperature variations than surface water, and the variation in pH between stations generally does not exceed one pH unit, ranging between 6.5 and8, which indicates the degree of alkalinity of the environment. The conductivity recorded values showed high and significant variations, ranging from 620 μs/cm to 6480 μs/cm, these high values (above 1000 μS/cm) are normal in eastern Algeria (Ramzi et al, 2020). The hardness, exhibits high values with a great variation from 208 mg/Lto 1048mg/L.…”
Section: Discussionmentioning
confidence: 86%
“…According to Rodier(2009), groundwater is less sensitive to temperature variations than surface water, and the variation in pH between stations generally does not exceed one pH unit, ranging between 6.5 and8, which indicates the degree of alkalinity of the environment. The conductivity recorded values showed high and significant variations, ranging from 620 μs/cm to 6480 μs/cm, these high values (above 1000 μS/cm) are normal in eastern Algeria (Ramzi et al, 2020). The hardness, exhibits high values with a great variation from 208 mg/Lto 1048mg/L.…”
Section: Discussionmentioning
confidence: 86%
“…More detailed evaluation of the reviewed studies revealed that 70% of studies in Africa concentrated on the description of newly discovered groundwater fauna (Figure 7a). Nevertheless, more than a dozen of studies in Algeria and Morocco conducted eco‐toxicological investigations, revealing that faunal richness in some urban and mining areas is linked with groundwater quality and stygofauna abundance decreases with pollution (Aidaoui, 2019; Boughrous, 2007; Boughrous et al, 2007; Boulaassafer et al, 2021; Boulal et al, 2017; Boutin et al, 1995; Boutin & Idbennacer, 1989; El Adnani et al, 2006, 2007; el Moustaine et al, 2013, 2014; Hallam et al, 2008; Hichem et al, 2019; Laid & Zouheir, 2018; Merzoug et al, 2011, 2014; Ramzi et al, 2020) with authors proposing the use of stygofauna as bioindicators of water quality (Merzoug et al, 2011, 2014). Boulaassafer et al (2021) study on evolutionary processes considerably expanded the knowledge of diversity and geographic range of a freshwater snail genus, and information on endemism and biogeographical distribution of stygobiotic crustacean species of Africa and Madagascar has been recorded (Tuekam Kayo et al, 2012).…”
Section: Global Groundwater Fauna Researchmentioning
confidence: 99%